Analisis Kualitas Air Sumur Gali di Kelurahan Arfai Kabupaten Manokwari, Papua Barat - David Victor Mamengko; Agnes Dyah Novitasari Lestari; Sabarita Sinuraya; Pribowo Angling Kusumo; Sri Haryono; Dewi Eviane (Environmental Insight Journal, 2026)
Groundwater quality is an important parameter for determining the initial character of an area before infrastructure development. This study aims to determine the initial condition of groundwater quality around the planned construction site of Building X in the Arfai Village, Manokwari, based on physical, chemical, and microbiological parameters. Groundwater samples were taken from two wells located near the activity site, namely the Financial and Development Supervisory Board well and the Religion Governemntal Offive office well. The samples were analyzed using applicable water quality testing methods and compared with the class 2 river water quality standards in Government Regulation of the Republic of Indonesia Number 22 of 2021 Appendix VI and the drinking water quality standards in Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023. For physical parameters, the water temperature was between 29.8–30.0°C, electrical conductivity was 332–580 µS/cm, and the concentrations of TDS, TSS, and turbidity were relatively low. Chemical parameters measured were neutral to slightly alkaline pH (7.16–7.66), BOD <2 mg/L, COD <3 mg/L, and DO of 4.3–5.1 mg/L, indicating low organic matter load. Concentrations of sulfate, nutrients, fluoride, and dissolved metals were relatively low, while oil and grease and total detergent did not indicate significant pollutant input. Microbiological parameters such as fecal coliform and total coliform were also at very low concentrations or below the detection limit. Overall, groundwater quality at both observation points remained in good condition and did not show significant anthropogenic pressure.